2020
DOI: 10.1002/jcb.29819
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers correlated with diagnosis and prognosis of endometrial cancer using bioinformatics analysis

Abstract: Endometrial cancer (EC) is one of the most common malignancies in the female genital system, characterized by high mortality and recurrence rates. This study attempted to screen key genes and potential prognostic biomarkers for EC using bioinformatics analysis. Twenty-seven normal endometrial tissues and 135 EC samples were collected from four Gene Expression Omnibus (GEO) databases, then we identified the differentially expressed genes (DEGs) and conducted downstream analyses. Moreover, we screened hub genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The GEO ( http://www.ncbi.nlm.nih.gov/geo/ ) database is a free public database of microarrays and is used for gene expression datasets and platform records [ 9 ]. The gene expression profiles of GSE29044, GSE42568, GSE50428 were chosen from the GEO database.…”
Section: Methodsmentioning
confidence: 99%
“…The GEO ( http://www.ncbi.nlm.nih.gov/geo/ ) database is a free public database of microarrays and is used for gene expression datasets and platform records [ 9 ]. The gene expression profiles of GSE29044, GSE42568, GSE50428 were chosen from the GEO database.…”
Section: Methodsmentioning
confidence: 99%
“…CAFs can foster radioresistance in ESCC tumor cells through the long noncoding RNA DNM3OS by modulating the PDGFβ/PDGFRβ/FOXO1 signaling pathway, suggesting that CAFs-promoted DNM3OS could be a crucial target to reverse radioresistance in ESCC tumor cells. A study by Zhao et al [ 24 ] in 2020, showed that three genes ( FOXL2, TCF4 , and NR2F2 ) exhibited a significant correlation with the prognosis of endometrial carcinoma; biological pathways associated with the low expression of these three genes were significantly enriched in cell cycle and fatty acid metabolism of cancer cells. However, there is limited evidence to validate the gene signatures involved in conferring radioresistance in ESCC patients to delineate accurate and efficient disease prognosis[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…18,19,40,41 Bioinformatic analysis has shown that GATA2 is expressed at low levels in both ovarian cancer and EC. 42,43 High GATA2 expression is associated with a good prognosis in ovarian cancer. 20 This finding is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…GATA2 is expressed at low levels in renal clear cell carcinoma, hepatocellular carcinoma, and neuroblastoma and inhibits distal metastasis and tumor recurrence 18,19,40,41 . Bioinformatic analysis has shown that GATA2 is expressed at low levels in both ovarian cancer and EC 42,43 . High GATA2 expression is associated with a good prognosis in ovarian cancer 20 .…”
Section: Discussionmentioning
confidence: 99%